HADIS YANG BERMASALAH DALAM PERSPEKTIF MU'TAZILAH - Jupita Apriani -; Muyessaroh; Fatichatus Sa'diyah (International Conference on Islamic Studies, 2025)
ABSTRACT This article discusses the problem of hadith from the perspective of the Mu`tazīlah, an Islamic theological flow known for its rational and critical approach to religious teachings using the library research method. The Mu`tazīlah emerged in the second century Hijri and had a unique view regarding the reception and interpretation of hadith. In this study it is revealed that the Mu`tazīlah rejected a number of traditions that were deemed to contradict their theological principles such as God's justice freedom of will and the oneness of God. The study analyzes how the Mu`tazīlah rational approach influenced their attitude towards hadith as well as the impact of their criticisms on certain traditions. In doing so, the article aims to provide a deeper understanding of the dynamics between hadith and creed in the Islamic tradition and its relevance for the development of contemporary theology. The results show that the Mu`tazīlah' s skepticism towards hadith not only reflects theological differences but also contributes to the broader discourse on the role of reason and revelation in Islam.This paper employs a qualitative approach, and to address the issues in this study, the author used library research. Keywords: Mu`tazīlah, Hadith, problematics